Development and validation of Manipal Inventory for Curriculum Evaluation (MICE): A comprehensive tool for evaluation of hybrid medical curriculum (Bangladesh Journal of Medical Science, 2023)
Background: In outcome-based education, the components of the curriculum must facilitate the students to attain expected outcomes. Hence, it is imperative to evaluate the components of the curriculum.Objective: The study aimed to develop and validate a comprehensive questionnaire, Manipal Inventory for Curriculum Evaluation (MICE) to evaluate the outcomes of a hybrid physiology curriculum.Methods: The development and validation of the questionnaire consisted of three stages. The first stage comprised generation of items through literature survey. A three-round modified Delphi technique was used in the second stage to gain consensus across the eleven panel members about the items in the questionnaire. The resulted questionnaire was administered to volunteers from first year undergraduate medical students which comprised the third stage. Principal Component Analysis with Varimax rotation and Kaiser Normalization, and Chronbach’s alpha were performed to analyze the data.Results: The preliminary questionnaire had two sections; section one had forty seven items, and section two had six items. After the Delphi rounds, the first section had only forty three items, however, there were no changes in the second section. Factor analysis of the first section resulted in seven factors. One item did not load on any of the components, and hence it was dropped from the questionnaire. Overall reliability was found to be 0.898 for Cronbach’s alpha.Conclusions: The questionnaire MICE was developed with two sections, one focusing on overall curriculum and the other on outcomes. On validation, it was found that the questionnaire had acceptable levels of validity and reliability.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 47-56